Antimycobacterial Activity of Essential Oils from Bulgarian Rosa Species Against Phylogenomically Different Mycobacterium tuberculosis Strains - Violeta Valcheva; Milka Mileva; Marine Dogonadze; Ana Dobreva; Igor Mokrousov (MDPI AG, 2024)
In this study, we aimed to assess the activity of the essential oils from four Bulgarian oil-bearing roses Rosa damascena Mill., R. alba L., R. centifolia L., and R. gallica L., on the reference strain Mycobacterium tuberculosis H37Rv and clinical M. tuberculosis strains of the Beijing and Latin-American Mediterraneum genotypes. The chemical composition of the essential oils was determined by gas chromatography (GC-FID/MS). Minimal inhibitory concentrations (MIC) were determined using the resazurin method. R. alba oil showed the highest inhibitory activity when tested on all strains of different phylogenetic origins with MIC in the range of 0.16-0.31 mg/mL, while R. gallica oil was the least active (MIC 0.62-1.25 mg/mL). The obtained results show heterogeneity of rose oil action on different mycobacterial strains and we hypothesize that the combined level of geraniol and nerol is a key factor that underlies the antimycobacterial action of the rose oils. Strain Beijing 396 was relatively more susceptible to the rose oils probably due to multiple and likely deleterious mutations in its efflux pump genes. Two clinical MDR strains have likely developed during their previous adaptation to anti-TB drugs certain drug tolerance mechanisms that also permitted them to demonstrate intrinsic tolerance to the essential oils. Further research should investigate a possible synergistic action of the new-generation anti-TB drugs and the most promising rose oil extracts on the large panel of different strains.